The Relationship Between Diabetes Mellitus, Geriatric Syndromes, Physical Function, and Gait: A Review of the Literature - de Souza Moreira, Bruno; Ferreira Sampaio, Rosana; Rossana Cavalcanti Furtado, Sheyla; Correa Dias, Rosangela; Noce Kirkwood, Renata (Current Diabetes Reviews, 2016)
Diabetes mellitus is a common and growing problem worldwide, especially in the elderly population imposing a huge economic burden for individuals and healthcare services. The purpose of this narrative review was to summarize the current state of knowledge about the relationship between diabetes and important geriatric syndromes, physical function measures, and gait variables. Studies pertaining to the topics were identified through on-line search of databases. Seniors with diabetes are more likely to experience falls, depression, and frailty. Furthermore, in older patients, diabetes has been associated with disability, including basic and instrumental activities of daily living, and with poorer performance on objective measures of physical function, such as sit-to-stand test, handgrip strength, Timed Up and Go (TUG) test, and Short Physical Performance Battery (SPPB). Diabetic seniors also have an altered gait pattern characterized by lower velocity and stride length, and higher step width, stance time, double support time, and stride length variability compared to non-diabetic seniors. Little is known about fear of falling in older adults with diabetes. The relationship between these outcomes and diabetes in older people is still outstanding and merits further investigation.
Keywords: geriatric syndromes